Comparison of efficacy of pharmacological treatments for chronic idiopathic constipation: a systematic review and network meta-analysis. Issue 9 (10th June 2016) - Nelson, Alfred D; Camilleri, Michael; Chirapongsathorn, Sakkarin; Vijayvargiya, Priya; Valentin, Nelson; Shin, Andrea; Erwin, Patricia J; Wang, Zhen; Murad, M Hassan
Abstract : Objective: To compare efficacy of pharmacotherapies for chronic idiopathic constipation (CIC) based on comparisons to placebo using Bayesian network meta-analysis. Data sources: We conducted searches (inception to May 2015) of MEDLINE, EMBASE, Scopus and Cochrane Central, as well as original data from authors or drug companies for the medications used for CIC. Study selection: Phase IIB and phase III randomised, placebo-controlled trials (RCT) of ≥4 weeks' treatment for CIC in adults with Rome II or III criteria for functional constipation; trials included at least one of four end points. Data extraction and synthesis: Two investigators independently evaluated all full-text articles that met inclusion criteria and extracted data for primary and secondary end points, risk of bias and quality of evidence. Outcomes: Primary end points were ≥3 complete spontaneous bowel movements (CSBM)/week and increase over baseline by ≥1 CSBM/week. Secondary end points were change from baseline (Δb ) in the number of SBM/week and Δb CSBM/week. Results: Twenty-one RCTs (9189 patients) met inclusion and end point criteria: 9 prucalopride, 3 lubiprostone, 3 linaclotide, 2 tegaserod, 1 each velusetrag, elobixibat, bisacodyl and sodium picosulphate (NaP). All prespecified end points were unavailable in four polyethylene glycol studies. Bisacodyl, NaP, prucalopride and velusetrag were superior to placebo for the ≥3 CSBM/week end point. No drug was superior at improving the primary end points on network meta-analysis. Bisacodyl appeared superior to the other drugs for the secondary end point, Δb in number of SBM/week. Conclusions: Current drugs for CIC show similar efficacy. Bisacodyl may be superior to prescription medications for Δb in the number of SBM/week in CIC.